The empancipation of women and the cultural elite at the turn of the twentieth century : the case of Amy Lowell (1874-1925) - Lombardo, Anna (Trinity College (Dublin, Ireland). Centre for Gender and Women's Studies, 2016)
Using the case study of American poet Amy Lowell (1874-1925), this thesis explores the path Lowell chose to develop her narrative identity and find her own voice in the male-dominated art world at the turn of the twentieth century. It also illuminates the effects of the performances of Italian actress Eleonora Duse (1858-1924) on Lowell’s artistic and cultural emancipation, and how Lowell negotiated her female desires in the face of the constraints of her time. Overall, this thesis provides novel insights into the rediscovery of lost female voices while exploring Lowell’s share in the cultural debates of her time. Lowell’s exclusion from literary history soon after her death in 1925 and her rediscovery over half a century later provide a lens through which to reconsider her work. Feminist critics, from Lilian Faderman in the 1980s to Melissa Bradshaw (whose most recent work on Lowell was published in 2011), have often been guided in their debates by an arguably prejudicial queer theory perspective invited by the theme of lesbian desire in Lowell’s love lyrics. In spite of Lowell’s active participation in literary and academic fields during her lifetime, her own poetry and criticism have seen little substantial feminist discussion and there have been relatively few critical studies of her work. A kind of critical tunnel vision seems to have obsessed both male and female critics, who were intent on digging into Lowell’s private life to find evidence of her sexuality reflected in her poems. This may explain why other aspects of her poetical and critical thought have been neglected. Exploring both her poetic and critical achievements, this case study ad-dresses aspects of Amy Lowell’s life and work that remain insufficiently considered in feminist studies. Lowell’s struggle to find her poetical voice and professional place in the arts is re-evaluated in light of the first wave of feminism in order to ascertain how she incorporated ideas of the New Woman that were quickly spreading throughout North America. Ultimately, this thesis explores to what extent Lowell’s vision of the poet’s role and poetry allowed her the opportunity to craft a uniquely feminist perspective that embraced artistic freedom and unveiled the status of female artists as second-class citizens in artistic circles. In discussing the controversial critical reception of Lowell in literary history, this thesis also questions feminist critiques that narrowly categorise writers according to their gender or sexual orientation. It is imperative to con-sider Lowell’s resistance to the various labels she received—feminist, lesbian, queer—when assessing her work and her struggle to popularise vers libre and Imagism among her American readers. This thesis employs several multidisciplinary investigative and analytical tools, borrowing from both literary criticism and gender studies, to examine Lowell’s texts and her active role in the cultural elite of her time, while also acknowledging wider theoretical debates regarding the role of gender, theatre, and poetry in this period, the early decades of the twentieth century. In weaving these strands together, this thesis argues that separating Amy Lowell from her claim to the right to explore every nuance of her womanhood is to read her work in fragments; it is to diminish her experiences as a woman and a female artist at the turn of the twentieth century, and thereby devalues her legacy and its relevance for women’s ongoing struggle for equality.
Keywords: Gender and Women's Studies, Ph.D.; Ph.D. Trinity College Dublin